DEIKSIS SOSIAL DALAM NOVEL LAYANGAN PUTUS KARYA MOMMY ASF: SEBUAH TINJAUAN PRAGMATIK - Halfian, Wa Ode; Sulastri, Sri; Asmarita, Asmarita (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
This study aims to describe the types and functions of social deixis contained in the novel Layangan Putus by Mommy ASF. The method used in this study is a qualitative descriptive method. The data collection technique used is the reading and note-taking technique to mark important parts that are social deixis. The data analysis technique in this study is to group data, describe and analyze data and conclude the results of data analysis. The data in this study were analyzed using the theory of Putrayasa and Filmore. The implications of this study are expected to contribute to the development of linguistics, especially in the field of pragmatics (deixis) which makes the novel the object of study. This study is also expected to be a reference for further researchers in the field of linguistics, especially in the study of deixis. Based on the results of the study and discussion, it can be concluded that the use of social deixis in the novel Layangan Putus by Mommy ASF was found as many as 25 data including social deixis of the type of profession totaling 6 data, nicknames or greetings totaling 14 data and titles totaling 5 data. The forms of social deixis found in the form of words and phrases function to differentiate a person's social level, as politeness or courtesy in language, maintaining social attitudes, differentiating a person's identity and clarifying a person's social position.